An experimentally validated numerical model for the parametrical evaluation of a full scale innovative Trombe wall of a nearly zero energy building based on composite natural zeolite plates - Kandilli, Canan; Gur, Muhammed; Yilmaz, Hakan; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2025)
This research conducts an extensive experimental and computational analysis of a novel full-scale Composite Trombe Wall (CTW) system, developed to improve passive solar heating efficiency in the context of nearly zero energy buildings (nZEBs). The CTW utilizes a natural zeolite-perlite CP, leveraging its high specific heat capacity and low thermal conductivity to increase thermal storage efficiency. Two configurations were examined: a standard composite wall and a variant incorporating a black-painted copper plate. The experimental tests were conducted under real climatic conditions in Usak, T & uuml;rkiye, and the measured data were used to validate a 3D time-dependent CFD model. The validated model was then employed to perform parametric analyses, focusing on optimizing the zeolite layer thickness (15-20 cm), air channel width (10 cm), and vent dimensions. Results indicate that the copper-integrated configuration significantly reduces thermal fluctuations and improves indoor temperature stability. The experimental results showed that the average temperature difference between the outdoor environment and the indoor space was 7.89 degrees C for the Standard CTW configuration and increased to 11.97 degrees C when the copper plate was integrated. Additionally, CFD-based parametric analysis of the air duct width revealed that temperature values remained relatively stable between 15 and 20 cm; however, reducing the duct width to 10 cm led to a significant rise in indoor air temperature, confirming the critical influence of this parameter on thermal performance. The study demonstrates the strong potential of the proposed CTW system to contribute to energy efficiency goals in cold climates, offering a practical, low-cost, and scalable solution for sustainable building retrofits.
Keywords: Full-scale composite Trombe wall; Composite natural zeolite plate; experimental analysis; Numerical analysis; Optimization; Energy saving